Stories from the Botanical Underground: Medicinal Plants as More-than-Human Knowledge Keepers - Saville, Dara (UnderCurrents: Journal of Critical Environmental Studies, 2025)
Plants are intelligent keepers and communicators of more-than-human knowledge. Their stories relate the agency of place and plants, showing us how to live where we are, what it means to contribute to the continuance of life, and how to collaborate with nonhuman others in resilient place-making. Botanical storytelling reaffirms people-plant relations, reimagines human relationships with the land, and intervenes in prevailing social and environmental narratives. Stories from the Botanical Underground, presented at the 2023 American Association of Geographers conference, relates the ecological-social lives of betony (Pedicularis), globemallow (Sphaeralcea), and vervain (Verbena) and the knowledge they hold for navigating socio-environmental challenges. This collection of stories intends to de-center human impositions of colonial power upon botanical landscapes and re-center the teachings of place and plants on a damaged planet. In this research, medicinal plants themselves are recognized as primary contributors of knowledge. [...]